2015
DOI: 10.1016/j.biomaterials.2015.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Dhvar5 antimicrobial peptide (AMP) chemoselective covalent immobilization results on higher antiadherence effect than simple physical adsorption

Abstract: a b s t r a c tBacterial colonization and subsequent biofilm formation is still one of the major problems associated with medical devices. Antimicrobial peptides (AMP) immobilization onto biomaterials surface is a promising strategy to avoid bacterial colonization. However, a correct peptide orientation and exposure from the surface is essential to maintain AMP antimicrobial activity.This work aims to evaluate the effect of the immobilization on antibacterial activity of Dhvar5 (LLLFLLKKRKKRKY), an AMP with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 36 publications
9
76
0
Order By: Relevance
“…The coupling between the in-plane OH bending and C-O stretching vibration of neighboring carboxyl group generated the bands at 1248 cm −1 and 1174 cm −1 , respectively [35]. The chitosan and maleimide coupling to the surface generated the 1080 cm −1 band typical for glucopyranose form chitosan [36] and the increment of the 1718 cm −1 band for additional C=O groups from the acetylated chitosan and maleimide units. Subsequent peptide immobilization led to the increment of the amide I stretching band at 1650 cm −1 which was hidden in the shoulder of 1718 cm −1 and is now more prominent.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling between the in-plane OH bending and C-O stretching vibration of neighboring carboxyl group generated the bands at 1248 cm −1 and 1174 cm −1 , respectively [35]. The chitosan and maleimide coupling to the surface generated the 1080 cm −1 band typical for glucopyranose form chitosan [36] and the increment of the 1718 cm −1 band for additional C=O groups from the acetylated chitosan and maleimide units. Subsequent peptide immobilization led to the increment of the amide I stretching band at 1650 cm −1 which was hidden in the shoulder of 1718 cm −1 and is now more prominent.…”
Section: Resultsmentioning
confidence: 99%
“…For all these reasons, AMPs are being applied in the production of antimicrobial surfaces, either by simple adsorption on the surface or covalent immobilization [116]. Nevertheless, studies suggest that covalent immobilization offers many advantages toward physical adsorption, including higher local and long-term stability, and lowering toxicity [116,117].…”
Section: Loading Antimicrobial Compounds Into Materialsmentioning
confidence: 99%
“…Several coatings can be classified as "contact biocides" since they use non-leachable substances that kill by contact with the bacteria and with no need to be released from the surface. This strategy is very interesting for both the self-sterilizing effect and the long-lasting activity, acting just through a direct contact with bacteria without consuming itself releasing from the surface without need [117,125].…”
Section: By Coatingmentioning
confidence: 99%
“…Although several approaches to create bactericidal coatings (based on different AMPs, substrates and conjugation strategies) have been described, the translation to clinically relevant materials such as polyurethane is still scarce. Yu et al have recently reported a bactericidal antiadhesive coating consisting of a polymer brush conjugated with the AMP E6 on PU, in the context of urinary catheters application .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AMP coatings can be considered a promising approach to prevent bacterial adhesion to biomaterials. AMP covalent immobilization offers many advantages compared to physical adsorption, including minimizing leaching, increasing local action, and providing long‐term stability . It was previously described that hybrids of the AMPs cecropin and melittin, namely CM [CM15 CA(1‐7)M(2‐9); KWKLFKKIGAVLKVLC], display higher antimicrobial performance than the parent peptides aside from the reduced hemolytic properties compared to melittin …”
Section: Introductionmentioning
confidence: 99%